Cyclooxygenase-2 Overexpression in Non-Melanoma Skin Cancer: Molecular Pathways Involved as Targets for Prevention and Treatment - Maglio, Daniel H. González; Paz, Mariela L.; Cela, Eliana M.; Leoni, Juliana (IntechOpen, 2011)
None